Teoria Geral dos Precedentes no Sistema Processual Civil Brasileiro - Garbi Junior, Carlos Alberto (2022)
The 2015 Code of Civil Procedure, introduced judicial precedent as a new primary source of the law, alongside the writen law, of mandatory observance for all magistrates. The present work aims to evaluate the impact that this new law intends on the way in which legal disputes are judged, mainly regarding the respect for precedents and jurisprudence in general. The advantages brought by the system of precedents will be presented, as the influence of the North American system took place, starting with the reception of the judicial system of constitutional review, culminating in the inspiration of the current system of precedents "the Brazilian way", the constitutionality of its inclusion via federal law, among several other matters. We deal with all the basic concepts needed to understand the topic